Effect of 20 minutes 3-prism base-out wear on vergence parameters - Muhamad Hakimi, Nik Amira Athirah; Othman, Shah Farez; Ithnin, Mohd. Hafidz; Tamchek, Nizam (CEDEC Training Sdn. Bhd., 2025)
Prism is utilised in visual treatment and binocular vision evaluation. Previous studies did not provide a satisfactory explanation for the impact of a 20-minute prism base-out wear on the vergence system when viewing at a distance. This study aimed to assess the effect of 3 prism base-out wear on the vergence system when viewing at distance position. Thirty (30) subjects were recruited in this cross-sectional clinical study. Subjects wore 3-prism base-out for 20 minutes while watching a movie at 6 m. Phorias were tested at distance and near, near point of convergence (NPC), negative fusional vergence (NFV) at distance and near, and positive fusional vergence (PFV) at distance and near. All vergence parameters were measured before and after watching the movie at 6 m with a 3-prism base-out inducement. A parametric paired t-test results analysis showed that there were significant differences in the mean phoria at 6 m (t (29) =2.37, p0.05). In conclusion, after a 20-minute period of 3 prism base-out wear, the vergence parameters observed in this investigation were almost identical for all normal subjects when viewing a distance fixation